Design, synthesis, characterisation and optimisation for titanium complexes for anti-cancer activity - Musa, Mustapha (2023)
This thesis describes the synthesis and biological evaluation of a library of titanium(IV) ONO complexes. The complexes were synthesised by reacting bis-phenolatoamine ligands with Ti(OiPr)4. The complexes were characterised by NMR spectroscopy, Mass spectrometry, Fourier-transform infrared spectroscopy and X-ray crystallography. The biological evaluation of the complexes was carried out using a variety of assays, including MTT, clonogenic, and cell count assays. The results showed that the complexes have significant activity against five different cancer cell lines (MDA-MB-468, Panc-1, HCT-116, HT-29, MCF-7) with varying GI50 values in the range 0.5 - 48 μM depending on the cell line and the ligand substituents used. The highest activity is seen against HCT-116 (GI50 0.5 μM) when R1 = OMe, R2 = ethyl and R3 = Me. The mode of action of the complexes was studied by cell cycle, annexine-V, γ-H2AX, reactive oxygen species, caspase techniques and confocal microscopy. All of the observed features, such as chromatin condensation, nuclear and cytoplasmic condensation, loss of cell volume, and nuclear fragmentation shrinkage of the cell, MAPKinase and proteomics signal transduction are consistent with the Ti(ONO)2 complexes inducing apoptosis through a G2/M phase block. In addition to the titanium(IV) ONO complexes, this thesis also describes the synthesis and biological evaluation of a library of 4-cyanophenyl-2-hydrazinylthiazoles. These compounds were synthesised by cyclising substituted thiosemicarbazones with α-bromo-4-cyanoacetophenone. The compounds were also found to have significant activity against HCT-116 and MCF-7 carcinoma cell lines, with the majority outperforming a cisplatin positive control. The results of this study suggest that the titanium(IV) ONO complexes and the 4-cyanophenyl-2-hydrazinylthiazoles have potential as anti-cancer agents. Further studies are needed to optimise the activity and selectivity of these compounds.